Differential distributed cayley space-time codes - Oggier, F.; Lequeu, E. (IEEE transactions on wireless communications, 2009)
We consider a wireless relay network with no channel information, which implements differential distributed space-time coding. We propose a coding strategy based on Cayley codes, which yields high data rate codes available for an arbitrary number of relay nodes.